Smart Materials in Pediatric Dentistry - Sourabh Ramesh Joshi; Sneh Thacker; Viddyasagar Prabhakar Mopagar; Neeta Surendra Padmawar; Chaitra Krishnagouda Patil; Gowri Swaminatham Pendyala (Journal of International Clinical Dental Research Organization)
Background: This systematic review aims to provide an overview of the current utilization of smart materials in pediatric dentistry and evaluate their advantages, limitations, and future perspectives associated with their use. Methods: This review was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta Analyses. From January 2013 to January 2024, a systematic search for reference articles was conducted in electronic databases such as PubMed/Medline, Cochrane, Scopus, and Web of Science. The population included children aged 3 to 14 who received smart material as a treatment modality. All titles and abstracts for the identified studies were reviewed to determine eligibility for inclusion. Results: A total of 100 articles from the electronic databases PubMed, Scopus, and Web of Sciences database were found using the initial keyword searches. Duplicates were removed from the search and records written in English only were included. Title and abstract screening were done to the 80 remaining articles. Out of these, 18 articles were extracted for full-text eligibility after 72 articles had been excluded based on their titles and abstracts. 11 were eliminated following full-text screening because they did not meet the age requirement. Therefore, this review contained a total of 7 articles. Conclusion: Even though they are still in the early stages of development, these materials have the potential to revolutionise dental care in the future. Paediatric dentists must stay up-to-date with these innovations in order to fully utilise them and provide comprehensive, high-quality care.